Balancing Corporate Rescue and Workers' Protection in Pandemic Crises: Lessons from Selected European Countries - Santoso, Budi; Pati, Umi Khaerah (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
Pandemics, one of the causes of economic crises, have led to the worst global catastrophe in a century. During the COVID-19 pandemic, numerous businesses exercised caution in financial investments and commercial activities to protect productivity and finances. As a result, these companies have progressively reorganized as a proactive strategy, often to reduce production costs and labor expenditures. This study aimed to analyze the balance of interests between corporate rescue and workers’ protection during pandemic crises within the framework of best practice regulations in selected EU countries. It also seeks to create a pandemic-preparedness model for companies and workers. The study reveals that wage subsidies (WS) can directly support workers, assess market demand, and reduce turnover due to COVID-19 or the implementation of large-scale social restrictions (PSBB). The Job Loss Security Program (JKP) in Indonesia has allowed for furloughs, providing laid-off workers with monetary benefits and training. Indonesia could consider integrating the WS and furlough systems, enabling firms and individuals to continue working with subsidies or to take temporary or full layoffs with benefits during crises.